US International Equity Investment and Economic Fundamentals - Nicole Hasler (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
Applying portfolio-based techniques to US foreign equity portfolio holdings, this paper studies the global investment behaviour of US investors. Taking wealth effects into account, we analyse active allocation decisions of investors. Using an updated data set by Bertaut and Tryon (2007) and Bertaut and Judson (2014), our results show that there is a negative link between US investor behaviour and lagged economic fundamentals and country risk indicators. This behaviour is, however, less pronounced during risk off episodes. Our study aims to provide a deeper understanding of US investors behaviour in foreign equity markets.
Keywords: G11; G15; F30; 330